Using Short Stories to Teach Vocabulary in Basic Reading 2 Class at Sanata Dharma University - Eklesia, Theresia Rosana; Angelina, Patricia (Indonesian Journal of English Language Studies (IJELS), 2019)
Vocabulary is one of the most important parts of language acquisition. Without vocabulary, people will not be able to deliver the message of the conversation. Therefore, students need to develop their vocabulary in order to be able to communicate in English. This research was conducted to investigate on how short story helped students on acquiring English Vocabulary in Basic Reading 2 Class. Therefore, the researcher had formulated two research questions: â€œHow do short stories help students to learn vocabulary in Basic Reading 2 class?â€ and â€œWhat are the activities using short stories that can be applied to teach vocabulary in Basic Reading 2 class?â€ Theories from Nation (1990) and Parvareshbar & Ghoorchaei (2016) were used to answer the research question formulated. Survey method was conducted in this research. The data were collected using observation sheet and field notes that were used to note the activities conducted in the class of thirty second semester students who were enrolled in Basic Reading 2 class, also an interview with the lecturer of Basic Reading 2 class. The result of this research is that there are five activities conducted by the lecturer.Â  Two of the activities are stated in the theory by Nation (1990) and the other three were found in the teaching and learning process. Future researchers are suggested to explore more methods that will benefit the students of Basic Reading 2 class in their process of learning new vocabulary.